Analysis of the Relationship Between Climate Change Impacts and Terrorism in ASEAN (1990-2018) - Anwar Luqman Hakim; Zora A. Sukabdi (Indonesian Journal of Multidisciplinary Science, 2023)
In August 1967, realizing that peace and stability is the catalyst to economic growth, 5 nations (Indonesia, Malaysia, Singapore, Thailand, and The Philippines) formed the Association of Southeast Asian Nations (ASEAN). The group eventually evolved and adding more members resulting with a grouping of 10 states with the addition of Brunei Darussalam, Cambodia, Lao’s PDR, Myanmar, and Vietnam. This paper intends to review the link between climate change and terrorism in member countries of the Association of Southeast Asian Nations (Association of Southeast Asian Nations/ASEAN). The datasets used to form the empirical model are the number of terrorist attacks from 1990-2018 recorded in the Global Terrorism Database (National Consortium for the Study of Terrorism and Responses to Terrorism (START) and Climate Change Indicators 1990-2018 recorded in The World Bank. Using multiple regression analysis, the study answered the research question as ‘An increase in access to electricity, rainfall, and farmland size has a statistical probability of increasing terrorism attacks in ASEAN, while an increase in greenhouse gas emissions, statistically has a probability of reducing terrorism attacks in ASEAN member states.